Damages for infringements of competition law - Urs Schweizer (European Journal of Law and Economics, 2022)
The EU Damages Directive (2014) requires that compensation shall place a person who has suffered harm in the position in which that person would have been had the infringement of competition law not been committed, i.e., firms' actions free of infringements serve as benchmark for specifying harm caused by deviations. The paper confronts this specification with game-theoretic models of market interaction. It is shown that firms are not necessarily deterred to form a cartel that coordinates action choice but non-deterred cartels turn out to be of less concern as they are at least welfare preserving if not enhancing. To implement damages rules that satisfy the Directive's compensation requirement, courts must have sufficient information. When the actions taken by firms cannot be directly observed, implementing the compensation requirements remains possible only if the available evidence is sufficiently informative.
Keywords: K21; L13; 340; Infringements of competition law; Damages; Private enforcement; Compensation requirements; Limited evidence